On the Adsorption Kinetics and Equilibrium of Polyaromatic Hydrocarbons from Aqueous Solution - Marta Haro; Belén Cabal; José B. Parra; Conchi O. Ania (Adsorption Science & Technology)
The purpose of the present work was to explore the removal of three polycyclic aromatic hydrocarbons (naphthalene, fluorene and acenaphtene) (PAHs) from aqueous solution onto an activated carbon. The adsorption performance of these compounds (both kinetic and equilibrium) has been discussed in terms of their chemical and physical properties. The results showed that the rate of adsorption was strongly dependent on the molecular size of the hydrocarbons. Thus, for example, steric hindrances associated with acenaphthene inhibited the accessibility of this compound to the high-energy sites. Under equilibrium conditions, the uptake seemed to be governed by the carbon–PAH affinity, as the lowest uptake was obtained for naphthalene which displayed the fastest adsorption rate. The interactions between the studied pollutants and the activated carbon seemed to be controlled by two factors, viz. aromaticity and water solubility. As a general rule, the higher the number of aromatic rings in the polycyclic hydrocarbon, the more favoured the adsorbate–carbon interactions. Analysis of the carbon after adsorption of the studied hydrocarbons indicated that the accessibility restrictions to the porosity of the carbon can also lead to weaker interactions with the activated carbon.